PREVENTING THE FAILURE OF CONVEYOR ROLLERS - Polvonov Nurbek Omonboyevich; Husanov Lazizbek Murodullo o`g`li; Ibragimov Sherzod Sayidolim o`g`li; Mamasharifov Bahromjon Ro’zimurod o’gli (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: In the dynamic mining industry, the efficiency and reliability of conveyor systems are critical to the smooth transport of raw materials. Among the most important components driving this technology, ball bearings play a key role. However, the harsh conditions of the mining industry pose enormous challenges to the durability and performance of ball bearings in conveyor systems. From abrasive materials to extreme temperatures, each factor contributes to the complex equation that determines bearing health and system performance. In this article, we delve into the complex world of ball bearings in mining conveyor systems, exploring the inherent challenges they face and the formulas-both literally and figuratively-that can be applied to ensure they perform optimally.